2009
DOI: 10.1021/ja910157h
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Amines and Hydroborane to the Disilyne RSi≡SiR (R = SiiPr[CH(SiMe3)2]2) Giving Amino- and Boryl-Substituted Disilenes

Abstract: The reaction of 1,1,4,4-tetrakis[bis(trimethylsilyl)methyl]-1,4-diisopropyltetrasila-2-yne 1 with diethylamine or diphenylamine produced the corresponding amino-substituted disilenes R(R'(2)N)Si=SiHR 2a, b (R = Si(i)Pr[CH(SiMe(3))(2)](2), R' = Et (2a), Ph (2b)). The reaction of 1 with 9-borabicyclo[3.3.1]nonane afforded the boryl-substituted disilene R(R''(2)B)Si=SiHR 3 (R''(2)B = 9-borabicyclo[3.3.1]nonan-9-yl). Spectroscopic and X-ray crystallographic analyses of 2a, b, and 3 showed that 2a and 3 have a copl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
38
0
5

Year Published

2010
2010
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 29 publications
(21 reference statements)
2
38
0
5
Order By: Relevance
“…Recently Sekiguchi et al reported the use of their disilyne as precursor to boryl-substituted disilenes by a hydroboration reaction, i.e., addition of the BH bond across the SiSi triple bond. 12 The first boryldisilenes 25a and 25b, however, were obtained by the same group through the reaction of disilenide 14a with the appropriate boronic acid chlorides in good yield (Scheme 9; 25a: 76%, 25b: 78%). 43 According to spectroscopic and structural data, the boryl groups adopt a perpendicular conformation with respect to the Si=Si bond and thus do not allow for efficient conjugation of the vacant p z orbital with the double bond.…”
Section: ç Reactions With Main Group Element Halidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently Sekiguchi et al reported the use of their disilyne as precursor to boryl-substituted disilenes by a hydroboration reaction, i.e., addition of the BH bond across the SiSi triple bond. 12 The first boryldisilenes 25a and 25b, however, were obtained by the same group through the reaction of disilenide 14a with the appropriate boronic acid chlorides in good yield (Scheme 9; 25a: 76%, 25b: 78%). 43 According to spectroscopic and structural data, the boryl groups adopt a perpendicular conformation with respect to the Si=Si bond and thus do not allow for efficient conjugation of the vacant p z orbital with the double bond.…”
Section: ç Reactions With Main Group Element Halidesmentioning
confidence: 99%
“…Among the few exceptions, silylenes such as 2, 3, and 4 have proven useful for the syntheses of compounds with heteronuclear double bonds between silicon and e.g., chalcogene. 11 Even though Sekiguchi et al recently revealed that disilynes 7 smoothly react with amines and boranes to yield otherwise difficult to obtain heteroatom-substituted disilenes, 12 only a limited number of functionalized derivatives with SiSi double bonds is known.…”
Section: ç Introductionmentioning
confidence: 99%
“…Hydroboranes 9-borabicyclo[3.3.1]nonane (9-BBN) and catecholborane (HBcat) react readily with 20 to give the hydroboration products 36a and 36b, which are stable and were fully characterized, including by X-ray diffraction and UVvis spectroscopy (Scheme 12). 33,34 In both cases, the product shows trans-addition of the H and borane substituents, which is counter to the mechanism known for hydroboration of alkynes. However, EZ isomerization of disilenes has a low enough energy barrier that it may even occur at room temperature.…”
mentioning
confidence: 68%
“…The disilyne 20 reacts with a variety of amines (primary or secondary) to give the 1,2-hydroamination products 37. 33,36 If the amine is sufficiently small, the addition of a second equivalent occurs to give the diaminodisilane 38 (of the amines tested only pyrrolidine was small enough). The addition of the second amine is regiospecific because of the polarity induced on the double bond by the first addition (see resonance structure 37¤¤).…”
mentioning
confidence: 99%
“…Mit der bemerkenswerten Ausnahme von boryl-und aminosubstituierten Disilenen, die durch die Addition von Boranen und Aminen an die SiSiBindung eines Disilins [9] erzeugt werden können, umfasst die Herstellung im Allgemeinen entweder photolytische Bedingungen oder stark reduzierende Reagentien oder Reaktanten wie lithiierte Spezies. [1] Eines der Hauptziele der derzeitigen Forschung ist daher die Entwicklung von neuen Synthesemethoden, die ohne solche Bedingungen auskommen.…”
unclassified